PENERAPAN PEWARNAAN GRAF UNTUK OPTIMALISASI PENJADWALAN KULIAH DI PROGRAM STUDI MATEMATIKA: Algoritma Welch-Powell - Amalia, Rizka Nanda; Affandi, Pardi (Equiva Journal, 2025)
Lecture scheduling is a critical challenge in higher education that requires efficient management of time and resources. This study applies graph theory, specifically the Welch-Powell graph coloring algorithm, to create a lecture schedule in the Mathematics Study Program, Lambung Mangkurat University. This method aims to avoid schedule conflicts between lecturers and students by utilizing graph representation. Each course is represented as a node, and conflicts between courses are represented as edges in the graph. The results show that the Welch-Powell algorithm is effective in producing an orderly and optimal lecture schedule. This approach allows for maximum use of space and time. In addition, this study also provides practical guidance for other institutions in applying graph theory to academic schedule management. With the results achieved, it is expected that lecture scheduling can be done faster and more accurately. This will support the improvement of better education quality. This research contributes to more efficient and planned academic management.